2015
DOI: 10.1101/gad.267914.115
|View full text |Cite
|
Sign up to set email alerts
|

Feedback control of growth, differentiation, and morphogenesis of pancreatic endocrine progenitors in an epithelial plexus niche

Abstract: In the mammalian pancreas, endocrine cells undergo lineage allocation upon emergence from a bipotent duct/endocrine progenitor pool, which resides in the "trunk epithelium." Major questions remain regarding how niche environments are organized within this epithelium to coordinate endocrine differentiation with programs of epithelial growth, maturation, and morphogenesis. We used EdU pulse-chase and tissue-reconstruction approaches to analyze how endocrine progenitors and their differentiating progeny are assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
123
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(138 citation statements)
references
References 63 publications
(72 reference statements)
15
123
0
Order By: Relevance
“…First, low-level Neurog3 expression within the secondary transition pancreatic epithelium seems widespread. Either Neurog3 BAC.Cre ;R26R lineage tracing or a Neurog3 EGFP/+ knock-in reporter detects a large number of intraepithelial cells that potentially represent cells in a Neurog3-expressing pre-endocrine-committed state (Zhang et al 2009;Wang et al 2010;Bankaitis et al 2015). In the study by Villasenor et al (2008), Neurog3 mRNA detection also suggests a Neurog3-expressing epithelial population that is broader than that visualized by Neurog3 immunodetection.…”
Section: Neurog3mentioning
confidence: 92%
See 3 more Smart Citations
“…First, low-level Neurog3 expression within the secondary transition pancreatic epithelium seems widespread. Either Neurog3 BAC.Cre ;R26R lineage tracing or a Neurog3 EGFP/+ knock-in reporter detects a large number of intraepithelial cells that potentially represent cells in a Neurog3-expressing pre-endocrine-committed state (Zhang et al 2009;Wang et al 2010;Bankaitis et al 2015). In the study by Villasenor et al (2008), Neurog3 mRNA detection also suggests a Neurog3-expressing epithelial population that is broader than that visualized by Neurog3 immunodetection.…”
Section: Neurog3mentioning
confidence: 92%
“…The trunk domain, a primary component of the epithelial plexus, consists of a pool of duct/endocrine bipotential Sox9 + Hnf1b + Nkx6.1 + cells (Seymour et al 2007;Solar et al 2009). Recently, we reported that distinct modes of epithelial morphogenesis in the peripheral versus core regions of the developing pancreas work in concert to generate the final "epithelial tree" of the mature pancreas (Bankaitis et al 2015). In the core, the epithelial plexus remodels into mature ductal tissues via growth and expansion (E12.5-E15.5) followed by plexus-to-duct transformation (E16.5-E18.5) (Bankaitis et al 2015).…”
Section: Neurog3mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies of mouse pancreas development suggest a strong reciprocal connection between the number of Neurog3 TA.LO progenitors and the architecture and integrity of the epithelial "plexus state" defined as the endocrine-birthing niche. 1,4,5 To date, production of multilineage islet-like clusters from hESC-derived pancreas progenitors has only been reported following implantation and maturation under the kidney capsule in vivo, allowing the transplant to adopt a complex 3-D structure. 6 Recent studies indicate that Neurog3 is just as critical to human pancreatic endocrine development as in mice, with true Neurog3 null mutations leading to neonatal diabetes and a block in b-cell differentiation from hESC.…”
mentioning
confidence: 99%